Retrospective study on clinical value and optimal use of [18F] FDG PET/CT for inflammation of unknown origin in Japanese patients - Tomoki Kobayashi; Daisuke Miyamori; Masanori Ito (Scientific Reports)
Abstract Despite advancements in medical technology, the challenges of diagnosing fever of unknown origin (FUO) and inflammation of unknown origin (IUO) persist. Positron emission tomography/computed tomography (PET/CT) has been used to assess these conditions; however, it is unclear which patients most benefit from this approach. This study aimed to assess the clinical value and optimal use of fluorine-18-labelled-fluorodeoxyglucose (18F-FDG)-PET/CT in patients with FUO/IUO. We reviewed FDG-PET/CT scans conducted at our department between January 2014 and December 2020 to further assess FUO/IUO. FUO was defined as a fever lasting over three weeks without a diagnosis based on conventional assessment. IUO was defined as prolonged inflammation with a body temperature below 38.3 ℃ and without a diagnosis after conventional diagnostic procedures. The efficacy of FDG-PET/CT was determined based on the diagnostic outcomes achieved by integrating imaging findings with histopathological or microbiological evidence, clinical criteria, or follow-up assessments. We conducted crude and age-sex adjusted logistic regression for potential risk factors to determine the degree of burden on demographic and clinical characteristics. Forty-five patients with FUO/IUO underwent FDG-PET/CT, and final diagnoses were made in 32 patients (71.1%). The percentages of diagnostic categories were 53.3%, 8.9%, and 6.7% for non-infectious inflammatory diseases, malignancy, and infection, respectively. In multivariable logistic regression analysis, IUO was the only independent predictor of the efficacy of FDG-PET/CT in the final diagnosis (odds ratio, 67.02; 95% confidence interval, 4.02–1119). Our results indicate that IUO was associated with a higher diagnostic yield compared to those with FUO.